A load frequency control strategy based on disturbance reconstruction for multi-area interconnected power system with hybrid energy storage system - Feng Zhu (Elsevier, 2021)
In order to handle the problem of frequency fluctuations caused by load disturbances in multi-area interconnected power systems, a sliding mode control strategy for hybrid energy storage system has been designed by combining interval observer and disturbance reconstruction technology. The hybrid energy storage system composed of a battery and a super capacitor has been used to improve the performance of load frequency control systems. Using the load frequency control model of the multi-area interconnected power system, the interval observers are designed for each area to get the information about interval bounds of the system state in each area online. Then, the load disturbance in each area is reconstructed online using the estimation information of system state, and a sliding mode controller based on interval disturbance reconstruction is designed for power consumption and storage of the hybrid energy storage system, so as to stabilize the power grid frequency. Simulation results have shown that the proposed control strategy can effectively suppress the frequency and tie-line power fluctuations caused by load disturbances, and ensure the reliability and stability of the power system.